PROYEK PENULISAN CERITA RAKYAT KABUPATEN PROBOLINGGO SEBAGAI KONSERVASI LITERASI LUMBUNG PENGETAHUAN - Widiastuti, Yuanita; Suyono, Suyono; Widyartono, Didin (At- Ta'lim : Jurnal Pendidikan, 2024)
Indonesia has its own story in every regional point. Unfortunately, the stories that have developed in society have not been preserved in the form of reading media. So the literacy potential that comes from folklore needs to be revitalized so that it can be read by people throughout the world and can be passed down from generation to generation. The project method carried out in four stages was proposed by researchers in this discussion. This method is carried out in the stages of determining sources, describing the plot, and imagining ideas. Researchers participate with students to make changes and encourage transformational action in folklore writing literacy. This activity is carried out in stages 1) introduction to folklore, 2) implementation plan, 3) presentation of each student's information about their area of origin, 4) preparation of the story framework, 5) writing of folklore and mentoring, 6) editing, 7) presentation of the work, 8) assessment of the manuscript, 9) submission of folklore to the village head. The project of writing Indonesian folk tales by students as an effort to conserve knowledge stores was carried out well. A total of 16 story titles were produced. These folk tales are also handed over to the village head in each village according to the story's origin. Folk tales are printed in banner form and displayed in the village office or local village library.